Optimization of Potato and Carrot Production in Karo District Using the Beale Method - riezky, riezkyfadhillah; Rina Filia Sari (KUBIK, 2025)
This study aims to optimize land allocation for potato and carrot production in Karo Regency, North Sumatra, using a quadratic programming approach using the Beale method. Secondary data from the Karo Regency Agriculture Office for 2018-2024 are used to construct a quadratic objective function using the least squares method. The Beale method is applied iteratively to solve optimization problems with linear constraints. The results show that the optimal land allocation of 0.5382 hectares for carrots and 0.4005 hectares for potatoes provides a maximum yield of 1.6239 tons. These findings demonstrate the effectiveness of the mathematical optimization approach in improving land use efficiency and supporting data driven decision making in the horticultural agricultural sector.